Harnessing the Power of Three-Dimensional Graphics and Multimedia in Preparing Teachers of Technology - Musurmankulov Qilichbek (Peerian Journals Publishing, 2024)
The integration of three-dimensional (3D) graphics and multimedia in teacher preparation programs holds immense potential for enhancing the skills and competencies of future technology educators. This article explores the benefits of utilizing 3D graphics and multimedia in preparing teachers of technology. It highlights how these technologies can facilitate engaging and impactful learning experiences, promote deeper understanding of complex concepts, and foster creative problem-solving skills. Additionally, the article discusses the challenges associated with incorporating 3D graphics and multimedia in teacher education and provides recommendations to overcome these obstacles. By leveraging the possibilities offered by 3D graphics and multimedia, teacher preparation programs can equip aspiring technology educators with the necessary knowledge and skills to thrive in the digital age
Keywords: three-dimensional graphics; multimedia; teacher preparation; visualization